LEGAL PROTECTION OF ENVIRONMENTS IN THE REPUBLIC OF SERBIA - Jović, Vojislav; Milutinović, Olivera; Kvrgić, Goran; Manojlović, Dragan (Economics of Agriculture, 2021)
Forms of environmental protection in the Republic of Serbia, as a rule, include administrative, misdemeanor and criminal law protection. This paper deals with general considerations of criminal law protection of the environment, its significance and position in the criminal legislation of the Republic of Serbia, and the effects of the competent judicial and other bodies on its suppression. The research includes basic national legal standards in the field of criminal law protection of the environment and their chronological correlation. The paper contains an empirical research of statistical indicators within which the correlation of reported, accused and convicted persons (outcome of criminal proceedings) for crimes against the environment during the time period from 2006 to 2017 in the Republic of Serbia was investigated.